Irrigation-induced river salinization: five major irrigated basins in the arid zone - Smedema, L. (International Water Management Institute, 2000)
This publication reports on a study of the increase in river salinity and the implemented control programs in five major irrigated basins in the arid zone. The study is limited to salinity.